2020
DOI: 10.1091/mbc.e20-01-0012
|View full text |Cite
|
Sign up to set email alerts
|

The ARF GAP ELMOD2 acts with different GTPases to regulate centrosomal microtubule nucleation and cytokinesis

Abstract: ELMOD2 is a ∼32 kDa protein first purified by its GAP activity towards ARL2 and later shown to have uniquely broad specificity toward ARF family GTPases in in vitro assays. To begin the task of defining its functions in cells, we deleted ELMOD2 in immortalized mouse embryonic fibroblasts (MEFs) and discovered a number of cellular defects, which are reversed upon expression of ELMOD2-myc. We show that these defects, resulting from the loss of ELMOD2, are linked to two different pathways and two differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
70
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 15 publications
(82 citation statements)
references
References 119 publications
8
70
4
Order By: Relevance
“…Thus, the GAP activity of ELMOD2 is required at centrosomes/microtubules but not at cilia. In addition, we showed that expression of activated ARF6 reversed the centrosome amplification phenotype in ELMOD2 KO MEFs, consistent with it being a consequence of failed abscission (Turn et al, 2020). Expression of the same ARF6 construct, though, had no effect on ciliary phenotypes (Figure 6).…”
Section: Discussionsupporting
confidence: 64%
See 4 more Smart Citations
“…Thus, the GAP activity of ELMOD2 is required at centrosomes/microtubules but not at cilia. In addition, we showed that expression of activated ARF6 reversed the centrosome amplification phenotype in ELMOD2 KO MEFs, consistent with it being a consequence of failed abscission (Turn et al, 2020). Expression of the same ARF6 construct, though, had no effect on ciliary phenotypes (Figure 6).…”
Section: Discussionsupporting
confidence: 64%
“…Though it was far more common to see 2-3 cilia per cell, some cells had 9 or more cilia (see Figure 1D). We previously reported (Turn et al, 2020) that ELMOD2 KO cells have supernumerary centrosomes at an increased frequency, which may enable this increase in ciliation. To examine whether the increased ciliation is solely a consequence of cell cycle defects, we repeated the scoring in cells with no evidence of cell cycle defects (i.e., one nucleus of normal size and morphology, only 1-2 centrosomes).…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations